Chlorhexidine and SARS-CoV-2 main protease: Molecular docking study - Vishakha Grover; Varinder Kumar; Veena Puri; Ashish Jain (Wolters Kluwer Medknow Publications, 2022)
As the beginning of the COVID-19 pandemic, numerous attempts have been made to identify specific antiviral mouth rinses which may help reduce the salivary viral load of severe acute respiratory syndrome coronavirus 2 (SARS-CoV2). Although the results from in vivo well-controlled clinical studies are yet pending, many contemporary antimicrobial mouth rinses have been explored for potential antiviral properties with respect to SARS-CoV-2. The most widely used compounds such as povidone-iodine, chlorhexidine, hydrogen peroxide, and essential oils have been known to have antiviral activity by targeting the outer lipid membrane or by denaturing the capsid proteins of enveloped virus SARS-CoV. Until now, there has been scanty scientific evidence on the molecular basis of interaction of the gold standard antimicrobial mouth rinse as an underlying mechanism of its anti-SARS-CoV-2 effect. The current communication reports the findings of our in silico docking study pertaining to understand the interactions of chlorhexidine with the most well-studied target of the SARS-CoV main protease.